2014
DOI: 10.1074/jbc.m113.533752
|View full text |Cite
|
Sign up to set email alerts
|

Src Family Kinases Promote Silencing of ATR-Chk1 Signaling in Termination of DNA Damage Checkpoint

Abstract: Background: Once DNA repair is completed, the DNA damage checkpoint is terminated, and the cell cycle is resumed. Results: Src inhibition induced a delay in G 2 checkpoint recovery and persistent ATR-Chk1 activation. Conclusion: Src inhibits ATR signaling to promote recovery from G 2 checkpoint arrest. Significance: Src sends a termination signal between the completion of DNA repair and the initiation of checkpoint termination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 96 publications
2
34
0
Order By: Relevance
“…SU6656 decreased autophosphorylation of SFKs [Active Src (pY416)] 3 h after SU6656 addition ( Figure 2F). We also examined the effect of SU6656 in the nuclear fraction, as our previous work suggested that SFKs suppress ATR-Chk1 signaling in the nucleus (Fukumoto et al, 2014a). Subcellular fractionation showed that SU6656 also decreased the autophosphorylation of SFKs in the nucleus ( Figure 2G).…”
Section: Lyn Suppresses Atr-chk1 Signaling During Recovery From the Rmentioning
confidence: 90%
See 3 more Smart Citations
“…SU6656 decreased autophosphorylation of SFKs [Active Src (pY416)] 3 h after SU6656 addition ( Figure 2F). We also examined the effect of SU6656 in the nuclear fraction, as our previous work suggested that SFKs suppress ATR-Chk1 signaling in the nucleus (Fukumoto et al, 2014a). Subcellular fractionation showed that SU6656 also decreased the autophosphorylation of SFKs in the nucleus ( Figure 2G).…”
Section: Lyn Suppresses Atr-chk1 Signaling During Recovery From the Rmentioning
confidence: 90%
“…Actin, Chk1, Chk1-pS317, Chk1-pS345, cPLA2, Desmoglein, g-H2AX, Hsc70, Lyn, and c-Yes antibodies were obtained as described previously (Takahashi et al, 2009;Fukumoto et al, 2014a). MoBU-1, Merck Millipore, NA61), Chk2 (cl.…”
Section: Antibodiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Immunodetection was performed as reported previously (10,26). Results were analyzed using an image analyzer ChemiDoc XRSplus (Bio-Rad).…”
mentioning
confidence: 99%